2022
DOI: 10.3390/life12111751
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Clove, Basil and Peppermint Essential Oils; Evaluating Their Toxicity on the Development Stages of Two-Spotted Spider Mites Grown on Cucumber Leaves

Abstract: The two spotted spider mite (TSSM), Tetranychus urticae Koch, is a cosmopolitan mite. It rapidly reproduces and can develop resistance to chemical pesticides. This study aims to evaluate the toxicity and acaricidal activity of three essential oils from basil, clove, and peppermint against T. urticae reproduction, which is grown on three cucumber cultivars, Chief (SC 4145), Raian (CB898), and Toshka (SC 349), under laboratory conditions at 27 + 3 °C and 70 + 5% RH. GC-MS characterized the volatile oils of basil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Garlic oil, chamomile, jojoba, and camphor essential oil nanoemulsion were effective against adult V. destractor. These results have been previously reported for terpinene, p-cymene, carvacrol, 1,8-cineoletimene, p-cymene, and αterpinene (Ebert et al, 2007;Anton and Vandamme, 2011;Chiesa et al, 2016;Bahreini et al, 2020) , á-pinene, 1,8-cineole, borneol, carvacrol, p-cymene and â-pinene (Mossa, 2016;Calatayud-Vernich et al, 2017;Bahreini et al, 2020;Campolo et al, 2020;Lucia et al, 2020;Awad et al, 2022;Giunti et al, 2022) It affected the development of many insects and mites.…”
Section: Tablesupporting
confidence: 85%
“…Garlic oil, chamomile, jojoba, and camphor essential oil nanoemulsion were effective against adult V. destractor. These results have been previously reported for terpinene, p-cymene, carvacrol, 1,8-cineoletimene, p-cymene, and αterpinene (Ebert et al, 2007;Anton and Vandamme, 2011;Chiesa et al, 2016;Bahreini et al, 2020) , á-pinene, 1,8-cineole, borneol, carvacrol, p-cymene and â-pinene (Mossa, 2016;Calatayud-Vernich et al, 2017;Bahreini et al, 2020;Campolo et al, 2020;Lucia et al, 2020;Awad et al, 2022;Giunti et al, 2022) It affected the development of many insects and mites.…”
Section: Tablesupporting
confidence: 85%
“…Choi et al [ 20 ] demonstrated that sage and lemongrass EOs exhibited high fumigant activity against T. urticae using the filter paper diffusion method. Lim et al also found that lemongrass EO treatment through fumigation resulted in an average mortality rate of approximately 85.8% [ 21 ]. An et al determined that lemongrass, sage, and eucalyptus EOs exhibit a higher level of toxicity against T. urticae [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Awad et al compared the effects of clove, basil, and peppermint EOs on T. urticae and found that clove EO exhibited oviposition inhibition activity comparable to that of avermectin. On the other hand, the oviposition inhibition efficacy of basil and peppermint EOs was poorer [ 21 ]. This is consistent with the findings of our study, indicating that clove and oregano EOs can effectively inhibit the reproduction of mites, thereby reducing the population of the subsequent generation.…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol (27.1%) and caryophyllene (24.5%) present in clove oil were the most toxic compounds against insect pests (Plata-Rueda et al 2018). In recent years, many scientists reported the amount of major compound of essential oils which were responsible for mortality, repellency and feeding deterrents in varying proportions (Charfi et al 2021, Awad et al 2022, Czarnobai et al, 2022. Varying degree of mortality and repellency reported by various scientists might be primarily due to the varying proportion of active compounds present in the essential oil of clove.…”
Section: Discussionmentioning
confidence: 99%